FUNGSI GANDA AGROFORESTRI KOPI: KONSERVASI CADANGAN KARBON DAN KEANEKARAGAMAN VEGETASI - Sari, Rika Ratna; Ishaq, Rizki Maulana; Purnamasari, Eka; Saputra, Danny Dwi (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2025)
Coffee agroforestry systems have great potential in optimizing the dual function of carbon and biodiversity conservation, especially in areas with high land use pressure. However, although coffee agroforestry has been widely practiced in Indonesia, the specific relationship pattern between carbon stocks and vegetation biodiversity is still not well understood. This study aimed to evaluate (1) the role of coffee agroforestry in maintaining vegetation diversity and carbon sequestration compared to disturbed forests (HT) and (2) the relationship between carbon stocks and biodiversity at various plant growth stages. Three land use systems were selected such as HT and complex (AFM) and simple (AFS) coffee-based agroforestry systems. The number of trees, species richness (R), Shannon-wiener index (H’), species evenness (E), and carbon stocks were measured in 12 plots (100 m x 20 m) for each vegetation growth stages (seedlings, saplings, poles, and trees). The results showed that the H index in coffee agroforestry was generally low to moderate (0.57-2.05), with the highest diversity in the tree category. The diversity level of AFM could mimic HT. In terms of carbon stock, HT had the highest stock (82±19 Mg ha-1), while total carbon stock showed a positive relationship with H index in all vegetation stages (R2=0,13-0,57). In contrast, the relationship between soil carbon stock and H index tended to be weak (R2=0,10). This study emphasizes the importance of maintaining total carbon stock through diverse vegetation in agroforestri systems to support climate change mitigation and biodiversity conservation.